2014
DOI: 10.1111/epi.12773
|View full text |Cite
|
Sign up to set email alerts
|

A multisite controlled study of risk factors in pediatric psychogenic nonepileptic seizures

Abstract: SUMMARYObjective: Psychogenic nonepileptic seizures (PNES) in youth are symptoms of a difficult to diagnose and treat conversion disorder. PNES is associated with high medical and psychiatric morbidity, but specific PNES risk factors in the pediatric population are not known. We examined if youth with PNES have a distinct biopsychosocial risk factor profile compared to their siblings and if the interrelationships between these risk factors differentiate the PNES probands from the sibling group. Methods: This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
81
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 38 publications
8
81
0
5
Order By: Relevance
“…School-related problems and interpersonal/family problems are commonly reported underlying stressors [56]. Physical and sexual abuse are believed to be common, but one recent study found no statistical difference in frequency of abuse between children with PNES and controls [57]. Chronic medical illness was found to be common compared to controls [57].…”
Section: Pediatric Considerationsmentioning
confidence: 99%
“…School-related problems and interpersonal/family problems are commonly reported underlying stressors [56]. Physical and sexual abuse are believed to be common, but one recent study found no statistical difference in frequency of abuse between children with PNES and controls [57]. Chronic medical illness was found to be common compared to controls [57].…”
Section: Pediatric Considerationsmentioning
confidence: 99%
“…Blant ungdom og voksne med tilstanden er 70 -80 % kvinner (4,19,20). Kjønnsfor-skjellen er ikke så uttalt blant barn (18).…”
Section: Forekomstunclassified
“…Oppvekst i en dysfunksjonell familie, faglige vansker på skolen, mobbing eller andre problemer i kameratflokken er hyppig assosiert med tilstanden hos barn (4,22). Fysisk eller seksuelt misbruk er ikke like vanlig blant barn med slike anfall som hos voksne (23), selv om en studie viste at 21 % og 6 % hadde opplevd henholdsvis seksuelt eller fysisk misbruk (3).…”
Section: Risikofaktorerunclassified
See 2 more Smart Citations